Integrated transcriptomic and metabolomic analyses reveal the antibacterial mechanism of isocorydine against Mycobacterium bovis - Wang, Xia; Ma, Weichao; Yuan, Yijun; Gao, Xiang; Zhao, Tianyu; Wang, Peng; Liu, Yanmei; Wang, Tingpu (Frontiers in Microbiology, 2025)
IntroductionMycobacterium bovis, the causative agent of zoonotic tuberculosis, poses a serious threat to public health and agriculture. This study investigates the antibacterial activity and mechanism of action of isocorydine (ICD), a natural alkaloid from Dicranostigma leptopodum (Maxim.) Fedde (DLF), against M. bovis.MethodsThe minimum inhibitory concentration (MIC) of ICD was determined. Phenotypic changes were assessed through assays measuring cell wall/membrane integrity, ion leakage, extracellular pH, total lipid content, and electron microscopy. The global response of M. bovis to sub-inhibitory ICD was elucidated using transcriptomic and metabolomic profiling.ResultsICD exhibited potent antibacterial activity with a MIC of 400 μg/mL. It disrupted the cell wall and membrane, leading to ion leakage, pH alteration, reduced lipids, and severe ultrastructural damage. Transcriptomics revealed 66 differentially expressed genes, with significant upregulation of efflux pumps and TetR family regulators. Metabolomics identified 1,158 differential metabolites, indicating a profound metabolic rewiring characterized by depleted central carbon metabolites and accumulated fatty acids.Discussion/conclusionOur results demonstrate that ICD exerts its antibacterial effect primarily by targeting the cell envelope, causing membrane disruption and energetic stress. M. bovis responds by activating efflux pumps and reprogramming its metabolism. This multi-omics study reveals the potential of ICD as an anti-mycobacterial agent and provides novel insights into the adaptive strategies of M. bovis under phytochemical stress.